Asuhan Kebidanan pada Ny. M Umur 24 Tahun di PMB Umi Dwi A - Umi Dwi Ariyanti; Eti Salafas (Universitas Ngudi Waluyo, 2025)
The role of midwives is very important in reducing maternal and child mortality, one of which is through continuous midwifery care. This care includes a